3D Printing of Materials with Tunable Failure via Bioinspired Mechanical Gradients. Issue 19 (16th January 2018) - Kokkinis, Dimitri; Bouville, Florian; Studart, André R.
Abstract: Mechanical gradients are useful to reduce strain mismatches in heterogeneous materials and thus prevent premature failure of devices in a wide range of applications. While complex graded designs are a hallmark of biological materials, gradients in manmade materials are often limited to 1D profiles due to the lack of adequate fabrication tools. Here, a multimaterial 3D‐printing platform is developed to fabricate elastomer gradients spanning three orders of magnitude in elastic modulus and used to investigate the role of various bioinspired gradient designs on the local and global mechanical behavior of synthetic materials. The digital image correlation data and finite element modeling indicate that gradients can be effectively used to manipulate the stress state and thus circumvent the weakening effect of defect‐rich interfaces or program the failure behavior of heterogeneous materials. Implementing this concept in materials with bioinspired designs can potentially lead to defect‐tolerant structures and to materials whose tunable failure facilitates repair of biomedical implants, stretchable electronics, or soft robotics. Abstract : A gradient 3D‐printing platform is developed and used to fabricate elastomer gradients with vastly different mechanical properties. It is used to investigate the role of bioinspired gradient designs on the mechanical behavior of heterogeneous materials. It is shown that bioinspired designs could potentially lead to more defect‐tolerant soft structures and to materials whose tunable failure facilitates repair of biomedical implants, stretchable electronics, or soft robotics.